Dental drill noise reduction using a commercially-available earplug device. Issue 1 (March 2023) - Jiang, Pingfei; Atherton, Mark; Millar, Brian J.
Aim: The dental handpiece noise in a dental surgery is concerning to both patients and staff as a major cause of dental phobia in patients and potential hearing loss in clinical staff. High-frequency noise generated by dental handpieces is considered to be the worst of the many noises in a dental clinic. Methods to reduce this noise have been proposed and either passive or active noise reduction headphones are often suggested. However, in a dental surgery environment, the need for good verbal communication with the patient needs to be maintained. As a result, this paper aims to evaluate one proprietary anti-noise device considered suitable for this specific purpose. Methods: Lab-based experiments were set up and carried out to evaluate QuietOn, using GRAS 43AG-1 Ear and Cheek Simulator to mimic a section of the human head and ear to represent the acoustic characteristics of an actual ear. Two types of dental drill noise recordings, one for electric motor-driven and another one for air turbine-driven, were played back through high-definition speakers. Sound data captured by the simulator are then visualised and plotted using MATLAB for analysis. Main findings: QuietOn is effective at low frequencies (< 1kHz). However, when dealing with high-frequency noise such as dental handpieces it is ineffective yet subdues verbal communication. Conclusions: Further development of passive or active noise cancellation earplugs is still needed to target dental handpiece noise while maintaining verbal communication.